Vaccine strategies for the control and prevention of Japanese encephalitis in Mainland China, 1951-2011. - Xiaoyan Gao; Xiaolong Li; Minghua Li; Shihong Fu; Huanyu Wang; Zhi Lu; Yuxi Cao; Ying He; Wuyang Zhu; Tingting Zhang; Ernest A Gould; Guodong Liang (Public Library of Science (PLoS), 2014)
Japanese encephalitis (JE) is arguably one of the most serious viral encephalitis diseases worldwide. China has a long history of high prevalence of Japanese encephalitis, with thousands of cases reported annually and incidence rates often exceeding 15/100,000. In global terms, the scale of outbreaks and high incidence of these pandemics has almost been unique, placing a heavy burden on the Chinese health authorities. However, the introduction of vaccines, developed in China, combined with an intensive vaccination program initiated during the 1970s, as well as other public health interventions, has dramatically decreased the incidence from 20.92/100,000 in 1971, to 0.12/100,000 in 2011. Moreover, in less readily accessible areas of China, changes to agricultural practices designed to reduce chances of mosquito bites as well as mosquito population densities have also been proven effective in reducing local JE incidence. This unprecedented public health achievement has saved many lives and provided valuable experience that could be directly applicable to the control of vector-borne diseases around the world. Here, we review and discuss strategies for promotion and expansion of vaccination programs to reduce the incidence of JE even further, for the benefit of health authorities throughout Asia and, potentially, worldwide.